2007
DOI: 10.1016/j.bbmt.2007.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparable Long-Term Survival after Bone Marrow versus Peripheral Blood Progenitor Cell Transplantation from Matched Unrelated Donors in Children with Hematologic Malignancies

Abstract: Despite the increasing use of peripheral blood progenitor cells (PBPC) instead of bone marrow (BM) for allogeneic hematopoietic stem cell transplantation (allo HSCT) from human leukocyte antigen (HLA)-matched unrelated donors in children, the relative benefits and risks of both stem cell sources in the pediatric setting remain largely unknown. Recently, the only larger study comparing the value of the 2 stem cell sources in a young patient group was confined to transplantation from HLA-identical sibling donors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 16 publications
4
29
0
Order By: Relevance
“…Paediatric studies looking at this question are small and non-randomized. Meisel et al (2007) compared PBSC to bone marrow in the unrelated setting in paediatrics, and saw the same incidence of chronic GVHD (about 60%) but more extensive chronic GVHD in the PBSC group (50% vs. 26%). A retrospective Center for International Blood and Marrow Transplant Research (CIBMTR) study showed lower survival in paediatric recipients of PBSC compared to marrow, with a higher incidence of cGVHD (Eapen et al, 2004).…”
Section: Incidence and Risk Factorsmentioning
confidence: 96%
“…Paediatric studies looking at this question are small and non-randomized. Meisel et al (2007) compared PBSC to bone marrow in the unrelated setting in paediatrics, and saw the same incidence of chronic GVHD (about 60%) but more extensive chronic GVHD in the PBSC group (50% vs. 26%). A retrospective Center for International Blood and Marrow Transplant Research (CIBMTR) study showed lower survival in paediatric recipients of PBSC compared to marrow, with a higher incidence of cGVHD (Eapen et al, 2004).…”
Section: Incidence and Risk Factorsmentioning
confidence: 96%
“…The day of neutrophil engraftment was defined as the first of 3 days in which the ANC was ⩾ 1000/mm 3 , and the day of platelet engraftment was defined as the first of 3 days in which the platelet count was ⩾ 50 000/mm 3 without platelet transfusions during the previous week. Acute and chronic GVHD were graded according to previously established criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Risk status at transplant was based on modifications to previously published classification schemes. 3,7 In brief, acute leukemia in first CR, CML in first chronic phase and myelodysplastic syndrome (MDS)-refractory anemia were considered standard risk. Acute leukemia in second CR or greater, or without complete remission, MDS with excess of blasts, juvenile myelomonocytic leukemia and secondary leukemia were considered high risk.…”
Section: Patient Cohortmentioning
confidence: 99%
See 2 more Smart Citations